MOLECULAR CHARACTERIZATION OF MULTI-DRUG RESISTANCE ENTEROCOCCUS FAECALIS ISOLATED FROM MASTITIC COWS MILK - Marwa H. A.; A. Abdulrazzaq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The study objects were to assess Enterococcus faecalis prevalence in milk from mastitis infected cows, and access their antibiotic resistance as well as investigate their resistance genes. A total of 300 samples were tested during the period from February to May in 2022. The results of initial examination showed that only 81 isolates as E. species according to phenotypic criteria. Confirmatory test was conducted, the results showed that only 25 isolates by 8.3% E.faecalis isolates. Antimicrobial susceptibility test indicated high levels of contamination with multi-drug resistant E.faecalis of with isolation of strains resistant to Vancomycin as 32%. The most high level of E.faecalis resistance was observed to Azithromycin, Cephalosporines, by 80 and 72% respectively. Adopt on results of susceptibility test, the six most isolates that gave high (MDR) were selected to investigate resistance genes in them by PCR, norA, tetK and aac6 genes are found in all of the isolate. E. faecalis gene was sequenced, analyzed, and registered in Gen-bank-NCBI and obtained the accession number (OP566380) that became a reference in Iraq and the world.